Agama dan Kekerasan Politik di Indoensia (Studi pada Kasus Pemberitaan di Media Internet) - Muhammad Kasim (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This paper discusses religion and political violence in Indonesia. The main problem in this research is the existence of political views which say that religion can be used as a tool in achieving power, so that violence often appears as a side effect. This research question is contained in the first two main questions, how violence in the name of religion can occur from a political perspective. Second, how is the phenomenon of cases of political violence in the name of religion in Indonesia. The method in this research is a case study method on several news published as news on the internet. The main sources in this research are the news about political violence in the name of religion which is published in Kompas.com, detiknews.com, people's minds.com, and CNN.com newspapers. Secondary sources in this research are articles discussing religion and political violence published in scientific journals. The results of this study come to the conclusion that religion is often used as a tool to achieve power in relationships. Then physical or non-physical violence occurs as a result which is a political act. Physical violence occurred in the internal attacks experienced by minority groups from the majority group such as attacks on Christians in Aceh, and non-physical violence occurred with the practice of applying rules that seemed to have been trumped up by government apparatus on church building regulations in Aceh.